Recent developments in monetary policy - Chrystal, K. Alec, 1946-; Mizen, Paul. (Cheltenham ; Northampton, MA : Edward Elgar, 2009)
The papers in these volumes reflect the key advances in broadly chronological order, while later papers indicate some of the current controversies that remain.
Includes bibliographical references and index.
uaj 24/05/2013
Loans
Keywords: Monetary policy; Money supply